Peningkatan Pengetahuan Ibu Hamil Trimester III Melalui Edukasi Manfaat Jus Buah Bit untuk Pencegahan Anemia di Desa Kuala Air Hitam - Julina Br Sembiring; Dalimawaty Kadir (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The World Health Organization (WHO) states that anemia is a serious global public health problem that especially affects women of childbearing age and pregnant women. The prevalence of anemia in women of childbearing age is 29.9%, in pregnant women 36.5%, in non-pregnant women 29.6%. Prevalence varies widely between countries and regions. Beetroot or also called Beta Vulgaris L. is a kind of tuber plant that is reddish purple in color. Shaped like a potato. Usually beets are consumed by juice or processed again into a meal with a soft texture. Anemia in pregnancy is very dangerous for the mother and the fetus. The impact of anemia on pregnant women is abortion, premature delivery, inhibition of fetal growth and development in the womb, susceptible to infection, antepartum bleeding, premature rupture of membranes, during delivery can cause His disorder, the first stage of labor can last a long time and neglected parturition occurs. In parturition, uterine subinvolution occurs which can cause postpartum hemorrhage, facilitate puerperal infection, and reduce breast milk production. The form of activity used in community service is the counseling method with lectures and questions and answers, by measuring knowledge, pre and post tests are carried out. The conclusion is that there is an increase in knowledge after being given education to mothers third trimester pregnant.